Negotiating power: a case study of Indonesian foreign domestic workers (FDWs) in Singapore - Rahman, Noorashikin Abdul (Curtin University, 2003)
This thesis examines the complex power structures that underscore the migration and employment of Indonesian women as foreign domestic workers (FDWs) in Singapore. The main objective is to highlight the power of individual Indonesian FDWs and the collective power of these women in negotiating these structures of power in the context of a migration study as well as a `resistance' study. I argue that Indonesian FDWs are active agents who exercise individual agency and collective `resistance' in the migration system. As labour migrants they exert power in shaping the nature of the migrant institution. One of the means in which they do so is by perpetuating the informal networks of migration. Individual Indonesian FDWs are also capable of exerting power in circumventing elements of exploitation and domination they encounter during their migration process and employment in Singapore. Crucial to this capability is the ability to have access to a network of agents within the migrant institution. Some Indonesian FDWs are also active in exerting power as a group to present a collective resistance against negative stereotyping of their identities as the immigrant other in Singapore. They do so via a formal religious based social group. This group encourages other Indonesian FDWs to portray the image of the disciplined worker couched within the moralising discourse of Islam by participating in productive activities on rest days. The aim of this is so that Indonesian FDWs can be treated with respect and dignity in Singapore. In general, my data show that Indonesian FDWs as active agents of the migration system do not attempt to challenge the overall structures that underscore their subordination and domination as overseas contract workers (OCWs) in Singapore.The power exerted by individual Indonesian FDWs is focused at ensuring their continued employment as FDWs under more desirable employment conditions. Their individual agency aimed at improving their work conditions is at a personal level and is based on personal goals that are thus too fragmented to challenge the institutionalised structures of employment. Moreover, my case studies reveal that some Indonesian FDWs endure more restrictive work conditions in order to achieve desirable aspects of working in Singapore. Their collective `resistance' against condescending treatment by the host society project an image of the disciplined FDWs desired by employers, maid agents and Singaporeans. Their subjective ambivalence and the ambivalence in their individual and collective acts of `resistance' in challenging aspects of subordination and domination show the complexity of the power relationships in which they are caught. I draw upon two bodies of theory to provide a framework for my analysis and argument. First, I draw upon the `migrant institution' framework espoused by Goss and Lindquist (1995) that is based on Giddens' structuration theory to illustrate the power exerted by individual Indonesian FDWs within the field of migration studies. I also draw upon Foucault's notion of power as a framework to examine collective ,resistance' displayed by Indonesian FDWs in Singapore. The data presented in the thesis are drawn from two sources, ethnographic fieldwork conducted in Singapore as well as relevant newspaper and other media accounts.